What You See Is What You Get.Get: Surface Transparency and Ambiguity of Nominalizing Reduplication in American Sign Language. (5th November 2017) - Abner, Natasha
Abstract: Nominalizing reduplication in American Sign Language (ASL) is an ambiguous process that can derive both concrete object‐ and result‐denoting nominals. The properties of this nominalization process, including this ambiguity, are accounted for here by appealing to the discrete and surface transparent morphology that the language uses to encode components of event (Wilbur2003 2010 ) and argument (Benedicto & Brentari2004 ) structure. Nominalizing reduplication is shown to be a process that nominalizes (and reduplicates) only the low portion of verbal structure responsible for encoding the event result (VPres ). Direct nominalization of this VPres constituent yields nominals with result‐denoting interpretations. Concrete object‐denoting interpretations may arise when the verbal structure contains an argument classifier, which is evident in the handshape of the verbal predicate. In such cases, the nominal argument introduced by the classifier serves as the input to (reduced) relative clause formation, yielding a concrete object‐denoting interpretation. The interpretive ambiguity is thus reduced to ambiguity in the syntactic structure underlying the derived nominal. This approach falls in line with longstanding structural approaches to nominalization and more recent proposals regarding processes of reduplication (Inkelas & Zoll2005 ).